Juanita la Larga : a novel - Valera, Juan, 1824-1905 (Book collections on Project MUSE., 2006)
Juanita la Larga (1896), the third of Juan Valera's eponymous novels with a female protagonist, unfolds in a small town in nineteenth-century Spain and tells the story of a young girl's romance with a wealthy widower many years her senior.